Potential Antioxidant Activity in Octyl p - Methoxycinnamate (OPMC) Compound Synthesized by Sonochemical Method - Indriyanti, Erwin; Adhityasmara, Dhimas; Praharsiwi, Masitoh S.; Wildan, Ahmad; Masduqi, Ahmad F.; Syukur, Mighfar; Mutiara, Erlita V.; Dinurrossifa, Rahmawati S. (Jurnal Akademika Kimia, 2023)
Octyl p - methoxycinnamate (OPMC) is a cinnamic acid derivative compound synthesized from p-methoxy cinnamic acid (PMCA) which is reacted with octanol in an acidic condition. OPMC has a substituted benzene group at the para position and conjugated at the carbonyl group. The method used to synthesize OPMC compounds is an esterification reaction with the help of ultrasonic waves at a sonication temperature of 60 0C for 4 hours. The synthesized compounds were then subjected to organoleptic tests, thin layer chromatography tests, solubility tests, melting point tests, FTIR - ATR, and GC - MS. The results showed that the OPMC results were in the form of fine white crystals. The qualitative test was carried out using thin-layer chromatography (TLC) showing an Rf value of 0.65 using n-hexane: ethyl acetate (4:1) eluent. OPMC synthesized is soluble in ethanol, methanol, chloroform, and ether and insoluble in water. The percentage yield of OPMC synthesized 55.72 % Melting point test with melting point apparatus showed that octyl p - methoxycinnamate started to melt at 50 0C. Analysis using FTIR - ATR showed 2919 and 2851 cm-1 (C - H alkyl) The absorption of the extended C=O ester group was at 1692 cm-1 close to the C=O ester (1712 cm-1). C=C group of alkenes and aromatics (1636, 1603, 1573, and 1510 cm-1). The stretching of the C-O ester group at wave number 1252 cm-1, Absorption for the stretching of the C-O ether group at wave number 1170 and 1167 cm-1. The wave number of 820 cm-1 indicates the presence of an aromatic group substituted at the para position. Tests with GC - MS found an abundance of compounds with 97.52 % base peak 290 m/z. Synthesized OPMC compounds have activity as a strong antioxidant with an IC50 value of 96.092 ppm.